The impact on insurance companies trading during unexpected events: An empirical study - Alsayed, Huda (Edelweiss Applied Science and Technology, 2025)
Significant disruptions to the economy, businesses, and people’s lives have been brought about by unforeseen events, such as the coronavirus disease 2019 (COVID-19) pandemic and political developments. National supervisory bodies should take action to mitigate the pandemic’s impact on the insurance industry. The operations of insurance companies are at risk because they must strike a balance between maintaining capital adequacy and solvency and a sharp rise in claims. This study counts as the first to address the issue of trading in uncertain events. This study examines the impact of the COVID-19 pandemic on insurance companies, utilizing stock market data from Saudi insurance companies spanning the years 2017–2025. For this paper, we use time series; precisely, the GARCH (EGARCH) model was applied to the data extracted from the TASI index for the Saudi market. The STATA program is used for our data analyses. The findings unequivocally demonstrate that the pandemic had a significant impact on the operation of the insurance industry. Additionally, it has been found that insurance company trading volumes reached their peak during the pandemic. COVID-19 had a much greater impact on the trading volume than other political events.